Features of Onset and Clinical Course of Reactive Arthritis in Children - I.S. Lebets; N.O. Panko (Zaslavsky O.Yu., 2013)
Objective: to identify the characteristics of the onset and clinical course of reactive arthritis in children at the present stage. Material and methods. 81 children with reactive arthritis aged from 2 to 18 years have been examined. During specification of nosology of articular pathology we used clinical, conventional laboratory and instrumental investigations, identified specific antibodies to Chlamydia, Mycoplasma, Yersinia, Ureaplasma, Cytomegalovirus, Herpes simplex virus, Epstein - Barr virus by ELISA. Results. Reactive arthritis of chlamydial etiology is characterized by lesion of large and medium-sized joints of the lower limbs, which is often accompanied by short-term morning stiffness and rapid onset of transient hypomyatrophy. Reiter's disease may develop rarely. Mycoplasma-induced reactive arthritis is characterized by debut with arthritis of knee, ankle, wrist and small joints of the hand, the development of bursitis and hypomyatrophy. Feature of Ureaplasma arthritis is the formation of bursitis in the heel and tendinitis. Reactive arthritis associated with elevated titers to antistreptolysin O differs with polymorphism of articular syndrome manifestations and, to some extent, of similarity with juvenile rheumatoid arthritis. Unspecified reactive arthritis has a number of the general features with others reactive arthritis and it is characterized by rather benign clinical course, long preservation of joints function and low laboratory activity. Relapse rate of reactive arthritis increases with an increase of duration of illness.